Erythema nodosum‐like lesions during BRAF inhibitor therapy: Report on 16 new cases and review of the literature. (6th March 2015) - Mössner, R.; Zimmer, L.; Berking, C.; Hoeller, C.; Loquai, C.; Richtig, E.; Kähler, K.C.; Hassel, J.C.; Gutzmer, R.; Ugurel, S.
Abstract Importance BRAF inhibitors have been licensed for the therapy of BRAF‐mutated melanoma. Recently, inflammatory skin lesions clinically resembling erythema nodosum have been reported as therapy side‐effects that may lead to treatment discontinuation. Objective To identify and characterize cases with BRAF inhibitor‐associated erythema nodosum‐like inflammatory skin lesions and development of an algorithm for their management. Design and Setting Retrospective chart review of melanoma patients treated with BRAF inhibitors in 14 departments of Dermatology in Germany and Austria and PubMed search for cases in the literature. Results Sixteen patients were identified who developed erythema nodosum‐like lesions under BRAF inhibitor therapy; 14 had received vemurafenib and two dabrafenib plus trametinib. The most frequently involved body sites were the legs. Histopathology was performed in five cases and revealed panniculitis in three and vasculitis in two patients respectively. Arthralgia and fever were associated symptoms in 44% and 31% of patients respectively. Inflammatory symptoms led to discontinuation of treatment in three patients, while in the majority of cases symptomatic management was sufficient. Skin lesions finally resolved despite continued BRAF inhibitor therapy in seven patients. In the literature, 19 additional patients with similar cutaneous appearance under BRAF inhibitors could be identified. An algorithm for the management of such lesions is proposed. Conclusion Erythema nodosum‐like skin lesions histologically correspond to panniculitis and/or vasculitis. Symptomatic treatment may be sufficient. However, additional work‐up and interruption of BRAF inhibitor therapy may be necessary in severe cases which are commonly associated with systemic symptoms.